Teacher Independence Program In Improving Community Trust - Muslimin Muslimin; Syafik Ubaidila (Institut Agama Islam Tribakti Kediri, 2020)
This type of research is descriptive qualitative. According to Kirt and Miller in his book Lexy J. Moleong,